Inculturation & Indian Art — An Indian Perspective - Nandikkara, Jose (Journal of Dharma, 1992)
Elavathingal Sebastian, Inculturation & Indian Art — An Indian Perspective, Rome: Urbaniana University Press, 1990. pp. 342.